2016
DOI: 10.1155/2016/7593681
|View full text |Cite
|
Sign up to set email alerts
|

Tree Species Diversity, Richness, and Similarity in Intact and Degraded Forest in the Tropical Rainforest of the Congo Basin: Case of the Forest of Likouala in the Republic of Congo

Abstract: Trees species diversity, richness, and similarity were studied in fifteen plots of the tropical rainforests in the northeast of the Republic of Congo, based on trees inventories conducted on fifteen 0.25 ha plots installed along different types of forests developed on terra firma, seasonally flooded, and on flooded terra. In all of the plots installed, all trees with diameter at breast height, DBH ≥ 5 cm, were measured. The Shannon diversity index, species richness, equitability, and species dominance were com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 16 publications
2
55
2
2
Order By: Relevance
“…Isichei (1995) also reported that Nigerian rainforest ecosystem is dominated by members of Sterculiaceae, Moraceae, Ulmaceae and Meliaceae families. The dominant families represented in this study sites differ from the families (Euphorbiaceae, Mimosoideae, Rubiaceae and Guttiferae) reported by Ifo et al (2016) in their study of a similar ecosystem.…”
Section: Discussioncontrasting
confidence: 87%
“…Isichei (1995) also reported that Nigerian rainforest ecosystem is dominated by members of Sterculiaceae, Moraceae, Ulmaceae and Meliaceae families. The dominant families represented in this study sites differ from the families (Euphorbiaceae, Mimosoideae, Rubiaceae and Guttiferae) reported by Ifo et al (2016) in their study of a similar ecosystem.…”
Section: Discussioncontrasting
confidence: 87%
“…The equitability index is the Shannon Maximum Diversity Index report. It marks the level of diversity achieved by the system relative to the maximum possible (Ifo et al, 2016).…”
Section:  Equitability or Pielou Indexmentioning
confidence: 99%
“…The values of the Piélou index are between 0 and 1. When they tend to 0, a dominance phenomenon is revealed and when they tend to 1, the index marks a regular compensation of individuals among species (Ifo et al, 2016).…”
Section:  Equitability or Pielou Indexmentioning
confidence: 99%
“…Cette pratique agricole est associée à des feux de végétation et à l'abattage des arbres pour la fabrication de pirogues, des constructions des maisons, la récolte du miel et l'obtention du bois de chauffe. Ces différentes activités ont par ailleurs un impact sérieux sur la biodiversité végétale des forêts de la zone d'étude (Ifo et al 2016).…”
Section: Dynamique De L'occupation Du Sol Dans Les Forêts De L'axe Imunclassified